2010
DOI: 10.1089/ars.2009.2945
|View full text |Cite
|
Sign up to set email alerts
|

The Hydrogen Sulfide Donor NaHS Promotes Angiogenesis in a Rat Model of Hind Limb Ischemia

Abstract: It is not known whether H(2)S can promote angiogenesis with improvement of regional blood flow in ischemic organs. Sodium hydrosulfide (NaHS, a H(2)S donor) was administered once a day for 4 w following femoral artery ligation. Collateral vessel growth, capillary density, regional tissue blood flow, the expression of endothelial growth factor (VEGF), VEGF receptor 2 (VEGFR2) and Akt were examined during or at the end of the treatment period. NaHS treatment significantly increased collateral vessel growth, capi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
163
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(171 citation statements)
references
References 40 publications
8
163
0
Order By: Relevance
“…32 In vivo, it was demonstrated that H 2 S is a proangiogenic factor in a model of hind limb ischemia. 33 These effects were associated with an increase in VEGF expression and activation of vascular endothelial growth factor receptor (VEGFR)2 signaling in vascular endothelial cells, suggesting that the effects of H 2 S may be mediated by VEGF and its receptor VEGFR2. 33 Bir et al recently showed that H 2 S-stimulated ischemic vascular growth is dependent on augmented expression and activity of VEGF.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…32 In vivo, it was demonstrated that H 2 S is a proangiogenic factor in a model of hind limb ischemia. 33 These effects were associated with an increase in VEGF expression and activation of vascular endothelial growth factor receptor (VEGFR)2 signaling in vascular endothelial cells, suggesting that the effects of H 2 S may be mediated by VEGF and its receptor VEGFR2. 33 Bir et al recently showed that H 2 S-stimulated ischemic vascular growth is dependent on augmented expression and activity of VEGF.…”
mentioning
confidence: 99%
“…33 These effects were associated with an increase in VEGF expression and activation of vascular endothelial growth factor receptor (VEGFR)2 signaling in vascular endothelial cells, suggesting that the effects of H 2 S may be mediated by VEGF and its receptor VEGFR2. 33 Bir et al recently showed that H 2 S-stimulated ischemic vascular growth is dependent on augmented expression and activity of VEGF. 34 We therefore hypothesized that by upregulating VEGF, H 2 S may directly antagonize the detrimental effects of sFlt1 on the endothelium, consequently attenuating the development of hypertension and proteinuria.…”
mentioning
confidence: 99%
“…Biological profiles of H 2 S and NO are similar, and both molecules are known to protect cells against various injurious states. Previous studies suggest that H 2 S augments angiogenesis under ischemic conditions both in vitro and in vivo 51, 52. Treatment with exogenous H 2 S or modulation of the endogenous production of H 2 S through the cardiac‐specific overexpression of CSE protects against acute myocardial infarction and HF by attenuating oxidative stress, inhibiting apoptosis, and reducing inflammation 34.…”
Section: Discussionmentioning
confidence: 98%
“…While the signaling properties under physiological conditions are being slowly uncovered, actions under pathological conditions are less defined. H 2 S has previously been described to contribute to angiogenesis [32], collateral growth [33], and vascular proliferation [34]. Under pathological conditions, these same signaling events can lead to the development of atherosclerosis, a key factor in the development of CVD.…”
Section: H 2 S In the Vasculaturementioning
confidence: 95%